Dermoscopic And Clinical Features Of Alopecia Areata In Pakistani Patients: A Cross-Sectional Study - Mahwish Ahmed; Neelam Ayub; Muhammad Hamza; Asma Nafisa; Dua Zhaira Zaidi; Ismat Zhaira Zaidi (Journal of Rawalpindi Medical College)
Objective: To evaluate the dermoscopic and clinical findings in Pakistani patients with Alopecia Areata